1968
DOI: 10.1002/1097-0142(196802)21:2<270::aid-cncr2820210217>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoid tumors of the vermiform appendix

Abstract: The carcinoid tumor of the appendix is a small, and usually innocuous, lesion most frequently discovered incidentally in an appendix removed for other reasons. It will only uncommonly contribute to the development of acute appendicitis. Although more frequently diagnosed in the female, the incidence of this tumor is equal in both sexes. The appendiceal carcinoid can occur in early childhood and reaches a peak incidence in young adults. Among patients older than 60 years the incidence seems to decrease more rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
115
2
26

Year Published

1976
1976
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(156 citation statements)
references
References 30 publications
(2 reference statements)
13
115
2
26
Order By: Relevance
“…The rate of aNENs presence in patients undergoing appendicectomy is reported to be 0.3-0.9% (Moertel et al 1968, Connor et al 1998, Tchana-Sato et al 2006, Debnath et al 2008, In't Hof et al 2008, Shapiro et al 2010, Yilmaz et al 2013; however, in some series, it has been reported to be as high as 2.3% (Hatzipantelis et al 2010, Ozer et al 2011, Van Gompel et al 2007 or as low as 0.16% (Coskun et al 2006, Doede et al 2000. The prevalence of aNENs among primary malignant lesions of the appendix ranges between 43 and 57% (Schmutzer et al 1975, Connor et al 1998.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of aNENs presence in patients undergoing appendicectomy is reported to be 0.3-0.9% (Moertel et al 1968, Connor et al 1998, Tchana-Sato et al 2006, Debnath et al 2008, In't Hof et al 2008, Shapiro et al 2010, Yilmaz et al 2013; however, in some series, it has been reported to be as high as 2.3% (Hatzipantelis et al 2010, Ozer et al 2011, Van Gompel et al 2007 or as low as 0.16% (Coskun et al 2006, Doede et al 2000. The prevalence of aNENs among primary malignant lesions of the appendix ranges between 43 and 57% (Schmutzer et al 1975, Connor et al 1998.…”
Section: Epidemiologymentioning
confidence: 99%
“…In terms of patient characteristics, a slightly higher incidence among females (Shaib et al 2015) has been shown in most but not all epidemiological studies (Sandor & Modlin 1998, Hemminki & Li 2001, Prommegger et al 2002, Van Gompel et al 2007, Landry et al 2008, Turaga et al 2012) -a fact that has been attributed to the increased rate of surgical interventions performed in women (Moertel et al 1968, Shapiro et al 2010, Carpenter et al 2012. A possible hormonal influence has not been proven (Graham et al 2009).…”
Section: Epidemiologymentioning
confidence: 99%
“…22 However Sandor et al found that depth of tumour invasion was not a prognostic factor in their retrospective analyses of 1570 ACTs. 13 The ENETs and NANETs guidelines included mesoappendix involvement as an indication for right hemicolectomy.…”
Section: Mesoappendix Involvementmentioning
confidence: 99%
“…Elli dört yaşında aktif yakınması olmayan erkek hastaya, kardeşinde metastatik kolon kanseri saptanması üzerine kontrol amaçlı yapılan kolonoskopide; çıkan kolon ilk ve orta kısımda iki adet [4][5] …”
Section: Olgu Sunumuunclassified